Realities and Specialties of Special Economic Zones - Gupta, Shely; Gupta, Prateek (Journal of Commerce and Trade, 2008)
India has shown an increasing trend in foreign trade since the last five decades as per the plan framed by the Government of India. India achieved a major milestone in her journey towards globalization when the Government decided to establish specially delineated duty free enclaves, appropriately named as Special Economic Zones (SEZs). SEZs are effectively contributing in generation of employment, export promotion, inflow of foreign capital and many more areas. Moreover, the Government is providing a number of incentives and various schemes have been launched to promote SEZs. The Government has decided to setup SEZs in almost every part of the country and to reinforce this decision, it has intended to establish more than 111 SEZs in the near future. A stable and hassle-free environment is essential to carry out exports and this, in turn, would require raising the level of production, reduction in duties and taxes and other forms of financial support. Keeping all these points in view, the Government of India designed a framework to setup SEZs. These Zones are involved specially in production of quality export-oriented goods and services at low costs. In this paper, an attempt has been made to analyse the basis which makes these Zones different and special.